Effect of blanching pretreatment and microwave-vacuum drying on drying kinetics and physicochemical properties of purple-fleshed sweet potato - Marzuki, Sigit Uji (J Food Sci Technol, 2020)
In this study, drying kinetics and quality of purple-fleshed sweet potato (PFSP) subjected to microwave-vacuum drying were investigated. The effects of hot water and steam blanching pretreatment on physicochemical characteristics of the dried products were also considered. The samples were dehydrated in a custom-made microwave-vacuum system at different power levels including 450, 600 and 850 W. Hot air drying at 70 °C was also conducted for comparison. The results showed that drying time of PFSP under microwave-vacuum conditions ranged from 6 to 12 min, significantly reduced as compared to that of hot air drying (600 min). The improvement of drying rate was also evidenced by increased effective moisture diffusivity (2.22 × 10(−7)–4.05 × 10(−7) m(2)/s) of the samples. Drying kinetics of PFSP was best fitted by Page and logarithmic model with R(2) ranging from 0.991 to 0.998, and RMSE from 0.016 to 0.030. PFSP dried under microwave-vacuum condition had lower water absorption index and swelling capacity than hot air drying. Color, antioxidant activity and total phenolic content of dried PFSP were also improved under microwave-vacuum drying. The effects of blanching pretreatment on quality of dried PFSP were more dominant in hot air than microwave-vacuum dried samples. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-020-04789-5) contains supplementary material, which is available to authorized users.